Constructing resource-efficient quantum circuits for AES - Jiang, Liao-Liang; Cai, Bin-Bin; Gao, Fei; Qin, Su-Juan; Jin, Zheng-Ping; Wen, Qiao-Yan (Frontiers in Physics, 2025)
An efficient quantum implementation of the advanced encryption standard (AES) is crucial for reducing the complexity of implementing an exhaustive key search through Grover’s algorithm. In this paper, we study how to construct resource-efficient quantum circuits for AES. We consider the product of T-gates depth and width (TDW) and the product of full depth and width (FDW) as optimization targets. We propose a generic method, called the controlled control qubit cascade (CCQC) technique, to construct quantum circuits for nonlinear components with reduced TDW and FDW. Using this, we construct a quantum circuit for the AES S-box. Compared with recent work presented at ASIACRYPT 2023, our S-box quantum circuit achieves reductions of 2.3% in TDW and 45.2% in FDW. Additionally, we propose a new key schedule strategy to reduce the full depth of the AES quantum circuit. Finally, the trade-offs between T-gates depth and width and the parallel numbers of S-box and TDW are analyzed.